The relationship between leg strength and cycling performance among Kelantan state level bicycle athletes / Wan Nur Amirah Wan Mohd Azmi - Wan Mohd Azmi, Wan Nur Amirah (Faculty of Sport Science and Recreation, 2019)
The purpose of this study are to identify the relationship between leg strength and cycling performance among state level bicycle athletes. Several bicycle athletes from Kelantan state male cyclist (N=II) were selected as the sample of the study using purposive sampling technique and their age ranged was between 15 to 18 years old. The leg strength were measured by strength test - squad and lunges. Statistical analysis of the tests was conducted by using Pearson Correlational Coefficient which to find the correlation between leg strength and cycling performance. A set of data was recorded and been analysed. There was no significant relationship between the leg strength and cycling performance among the cyclist which for strength test - squad at the value of 0.516 and for the strength test -lunges at the value of 0.187. Hence, it was concluded that the leg strength of the state level bicycle athletes shows a negative correlation with the cycling performance.